Kewenangan Jaksa Sebagai Pengacara Negara Dalam Upaya Pengembalian Kerugian Keuangan Negara (Studi Putusan Pengadilan Negeri Tanjungbalai Nomor: 25/Pdt.G/2020/PN.Tjb) - Nurul Ayu Rezeki; Hasim Purba; M Ekaputra; Vita Cita Emia Tarigan (Jurnal Pencerah Bangsa, 2024)
This thesis research is entitled "Authorities of the Prosecutor as a State Lawyer in Efforts to Recover State Financial Losses (Decision Study Number: 25/Pdt.G/2020/PN.Tjb). The research method used is normative and empirical legal research methods. This research is explorative, descriptive and prescriptive. The results of the study show that the Authority of the State Attorney's Prosecutor based on Article 33 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes is as a state representative to file a lawsuit against the heirs of a corruption suspect who has died. In the aquo case, it has actually been found that losses to state finances are basically restitution of state financial losses to be prioritized and expedited. The amount of state financial losses can be calculated based on the findings of the competent authority or the appointed public accountant, you do not have to force the calculation of state financial losses from the Supreme Audit Agency so that the principle of justice is fast, cheap and low cost is created